2022
DOI: 10.21037/atm-22-3967
|View full text |Cite|
|
Sign up to set email alerts
|

Correlation between gut bacteria Phascolarctobacterium and exogenous metabolite α-linolenic acid in T2DM: a case-control study

Abstract: Contributions: (I) Conception and design: Q Hu; (II) Administrative support: D Xiong; (III) Provision of study materials or patients: L Li; (IV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In relation to the correlation of some nutrients with specific genera, we can observe that in the study of olive oil consumption, we found a positive correlation with genera that have been seen to be found with a lower abundance in certain diseases such as inflammatory bowel disease, hypercholesterolaemia, gastric cancer, or type II diabetes mellitus [ 19 , 55 , 65 , 66 , 67 , 68 , 69 ]. This suggests that these microorganisms are markers of good health status.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In relation to the correlation of some nutrients with specific genera, we can observe that in the study of olive oil consumption, we found a positive correlation with genera that have been seen to be found with a lower abundance in certain diseases such as inflammatory bowel disease, hypercholesterolaemia, gastric cancer, or type II diabetes mellitus [ 19 , 55 , 65 , 66 , 67 , 68 , 69 ]. This suggests that these microorganisms are markers of good health status.…”
Section: Discussionmentioning
confidence: 85%
“…In relation to the intake of NSPs, we found a positive correlation of genera such as Lactococcus , Victivallis , Anaerofustis , Senegalimassilia , and Phascolarctobacterium , which are related to SCFA production, good health status, and higher longevity [ 63 , 67 , 69 , 74 ]. However, Finegoldia and Peptoniphilus are also associated with inflammatory processes and the presence of conventional adenomas [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Phascolarctobacterium is associated with alpha-linolenic acid, which better promotes the repair of metabolic disorders and increases the abundance of beneficial intestinal bacteria. 34 After all, supplementation, mainly FSM4, may be achieved by increasing the healthy bacteria, promoting the production of functional metabolites for suppressing inflammation to alleviate diarrhea. With respect to the microbiome, soy compounds, including proteins, small peptides, and polyphenols (isoflavones), can regulate the balance of gut microbiota, restore healthy gut bacteria, and reduce the colonization of intestinal pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…What’s more, the components in serum are supposed to affect the types and numbers of intestinal flora [ 31 ]. And it is feasible to affect the types and numbers of intestinal flora by using natural products to alleviate or treat diseases [ 32 ]. Therefore, in this study, we focus on the intestinal flora and metabolites to study the therapeutic effect of A. lancea on GI diseases and explore its underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%